Young, talented and injured: Injury perceptions, experiences and consequences in adolescent elite athletes - von Rosen, P.; Kottorp, A.; Fridén, C.; Frohm, A.; Heijne, A. (European Journal of Sport Science, 2018)
Even though injury is common in elite sports, there is still a lack of knowledge of young athletes` injury perception both during and after injury. The aim of this mixed-method study was, therefore, to explore, in-depth, data on injury consequences and adolescent elite athletes` perceptions and experience of injury. Three hundred and forty adolescent elite athletes (age range 15-19), from 16 different sports, were bi-weekly monitored over 52 weeks using a valid questionnaire. Twenty athletes from the same cohort were interviewed in focus groups about injury experience and perceptions. The results show that the average bi-weekly prevalence of injury was 38.7% (95% CI 37.3-40.1), with 30.0% (n = 102) of the athletes injured for more than half of all reporting times. An overarching theme from the focus groups highlighted the risk among young athletes of a loss of identity while injured. The findings support several suggestions that may improve the rehabilitation process and enhance rehabilitation outcomes: (a) provide clear pathways to the medical team, (b) recognize the identity loss, (c) involve the injured athletes with the rest of the teammates and (d) educate athletes about how to interpret pain signals. Future research should explore and evaluate the effectiveness and generalization of such interventions.